2006
DOI: 10.1261/rna.2320506
|View full text |Cite
|
Sign up to set email alerts
|

Assessing IRES activity in the HIF-1α and other cellular 5′ UTRs

Abstract: Dicistronic reporter plasmids, such as the dual luciferase-containing pR-F plasmid, have been widely used to assay cellular and viral 59 untranslated regions (UTRs) for IRES activity. We found that the pR-F dicistronic reporter containing the 59 UTRs from HIF-1a, VEGF, c-myc, XIAP, VEGFR-1, or Egr-1 UTRs all produce the downstream luciferase predominantly as a result of cryptic promoter activity that is activated by the SV40 enhancer elements in the plasmid. RNA transfection experiments using dicistronic or un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 34 publications
6
112
0
2
Order By: Relevance
“…Our data also revealed that arsenite stress induced RBM4 binding to cellular mRNAs encoding Bcl-2 and c-Myc. Although whether translation of these two mRNAs is mediated by authentic IRES is still being debated (23,32), RBM4 may activate their expression either through IRES or via a not-yet-known mechanism but also involving eIF4A in response to cell stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also revealed that arsenite stress induced RBM4 binding to cellular mRNAs encoding Bcl-2 and c-Myc. Although whether translation of these two mRNAs is mediated by authentic IRES is still being debated (23,32), RBM4 may activate their expression either through IRES or via a not-yet-known mechanism but also involving eIF4A in response to cell stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia induces the expression of a subset of genes directly regulated by the transcription factor HIF-1α (hypoxia-inducible factor-1α). The translation of the HIF-1α mRNA is cap-dependent (26), and may be fine-tuned by Mnk1/2-mediated phosphorylation of eIF4E (27). In addition, HIF-1α mRNA contains an internal ribosomal entry site (IRES) in its 5′ untranslated region.…”
Section: Mnk1/mnk2 Double Deficiency Does Not Affect Cellular Responsmentioning
confidence: 99%
“…In several instances, these cellular IRES elements facilitate translation under stress conditions, including hypoxia, when protein synthesis via cap-dependent translation is reduced (111). Specifically, vascular endothelial growth factor (112), HIF-1a (113), and BiP (114,115) have all been reported to have IRES activity, although this is still controversial (116). The availability of eIF4E has been proposed to control a ''switch'' between cap-dependent and IRES-mediated translation (117).…”
Section: Selective Gene Expression Mediated By Eif4f Regulation Durinmentioning
confidence: 99%